Notes on the genus Micromorphus Mik (Diptera: Dolichopodidae) and the uncertain identity of its type species, M. albipes (Zetterstedt) - Bickel, Daniel J. (Zootaxa, 2022)
Micromorphus albipes (Zetterstedt), the type species of the genus Micromorphus Mik (Diptera: Dolichopodidae), was based on a female collected in Sweden. Diagnostic males have not been directly associated with the species, even though at least three distinct congeners based on male genitalia occur in northern Europe. Despite being inadequately described, the name has been applied to species in the New World, New Zealand and Nepal. Micromorphus albipes is demonstrated not to occur in the New World, and Micromorphus caudatus (Aldrich), new status, is redescribed and regarded as the valid name for these incorrect identifications. The records of Micromorphus albipes from New Zealand and Nepal are also unsubstantiated. As well, the enigmatic Central American Micromorphus micidus Parent is redescribed and figured. The genus Micromorphus as a whole is discussed.